أثر قياس تكاليف الجودة والتقرير عنها على تنافسية الشركات الصناعية الأردنية - الرحاحلة محمد ياسين; الشرايري جمال عادل (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى التعرف على تأثير وأهمية قياس تكاليف الجودة والتقرير عنها في تعزيز التنافسية للشركات الصناعية الأردنية، حيث وزع الاستبيان على (87) شركة بواقع (3) استبيانات لكل شركة واستعيد منها (186) استبياناً صالحاً للتحليل أي بنسبة (71%). ودلت النتائج على أنه يتوفر لدى الشركات الصناعية المساهمة الأردنية البنية اللازمة لقياس عناصر تكاليف الجودة الظاهرة والمستترة، وأنها تقيس هذه التكاليف وإن هنالك تأثيراً لعملية القياس على تنافسية الشركات الصناعية الأردنية. وقد أوصت الدراسة بضرورة اهتمام إدارات الشركات في القطاعات الأخرى بتطبيق مفهوم تكاليف الجودة وقياسها والتقرير عنها واستخدامها في تعزيز قدراتها التنافسية. The study aims to investigate the impact of measuring and reporting quality cost on competitiveness of Jordanian companies. A questionnaire was developed and distributed to (87) companies, (3) for each company, out of them (186) were valid and suitable for analyses that represent (71%). The study showed that the Jordanian industrial companies have the necessary environment to measure quality costs and measure some elements of disclosed and hidden quality costs and reporting about it and used cost report in decision-making. There are significant impacts of measuring quality costs on the competitiveness of these companies. The study recommended the managements of Jordanian companies should implement the concept of quality costs, measure, report about it, and use the reports of in improve there competitiveness.